Mucopolysaccharidosis Type I in a Dog - Amaral, Andreza da Silva; de Sales, Nathali Adrielli Agassi; Rosado, Isabel Rodrigues; Giugliani, Roberto; Burin, Maira Graeff; Baldo, Guilherme; Martin, Ian; Alves, Endrigo Gabellini Leonel (Acta Scientiae Veterinariae, 2021)
Background: Mucopolysaccharidoses (MPS) are a group of rare illnesses caused by deficient activity of enzymes required for degradation of glycosaminoglycans (GAGs). Each type of MPS is caused by mutations in one of the genes that encode the 11 acid hydrolases involved in this degradation process, which are present in the lysosomes. Progressive accumulation of GAGs in the lysosomes result in cellular dysfunction and multisystemic clinical signs, with consequent decrease in quality of life and lifespan of the affected patients. The objective of the present work is to report a case of MPS type I in a dog. Case: A mixed-breed male dog of approximately 2-month-old weighing 2.5 kg was referred to Hospital Veterinário de Uberaba with a distended abdomen. At the clinical examination, the patient exhibited a regular nutritional status, pale mucous membranes, 7% dehydration, an arterial pulse rate of 120 beats per minute, a respiratory rate of 40 breaths per minute, and a heart rate of 120 beats per minute. There were increased abdominal volume and tension, and hepatosplenomegaly. The abdominal percussion exam produced a dull tone. Additional findings included muscular atrophy, increased volume in the metaphyseal areas of the thoracic and pelvic limbs, valgus limb deformity in the thoracic limbs, and instability of the hip joint. Radiographic examination revealed a series of bone alterations such as reduced vertebral bodies, a generalized decrease in radiopacity, thin cortical areas in long bones, narrowing of the pelvic canal, and marked deformation and irregularities in acetabular and epiphyseal (both proximal and distal) areas of the femurs and tibias. Ankylosis of the tibiotarsal and tarsometatarsal joints was also observed. There was also loss of trabecular structure and irregularities on the surfaces of all epiphyses of the bones, epiphyseal lines markedly open, and bones that were shorter and thicker than normal. The suspected diagnoses were pseudoachondroplasia and mucopolysaccharidosis. In view of the clinical and radiographic findings, tests were performed to investigate the clinical suspicion of MPS. Consequently, qualitative and quantitative tests of GAGs in the urine, as well as a blood enzymatic essay, were requested; results confirmed the diagnosis of MPS type I. Intensive treatment allowed the patient to reach adulthood. Whenever new clinical signs emerged, they were treated palliatively. As the disease became more severe, the patient died at the age of 3 years. Discussion: Mucopolysaccharidosis type I is a rare disease that exhibits variable clinical signs and for which there is no specific treatment in dogs; these characteristics hinder diagnosis and treatment of patients as the one described in this report. The major clinical signs observed in this case are in agreement with those reported in the literature, according to which the disease can cause severe alterations such as bone defects, increased volume and deformities in the joints of the limbs, corneal opacity, and enlargement of abdominal organs such as the liver and spleen. In considering diagnostic methods for MPS, the main screening test is quantification of GAGs in the urine. The confirmatory test for MPS consists of analysis of the activity of specific lysosomal enzymes in a blood sample; this test allowed the establishment of a diagnosis in this case. Enzyme replacement therapy, in which a recombinant enzyme is used, have yielded good results in humans and dogs. However, this treatment does not cure the disease – it only attenuates the clinical signs and enables the patient to reach adulthood. Access to enzyme replacement therapy was not possible in the present case. As a conclusion, MPS should be included in the differential diagnosis of developmental diseases in puppies. This highlights the importance of further studies and reports on this disease.